Prevalência de experiências traumáticas na infância e fatores associados entre adultos atendidos na atenção primária de Cuiabá - Alves, Eliane dos Santos (2022)
Investigations on traumatic childhood experiences, such as physical, emotional, sexual abuse and neglect, have shown an association with physical and mental health at a later stage of human development. However, due to the diversity with which it occurs, it is necessary to explore its magnitude and distribution according to population characteristics. Objective: to estimate the prevalence of traumatic experiences in childhood and associated factors in users of primary care in the city of Cuiabá, capital of Mato Grosso. Methods: This is a cross-sectional study with adults treated at Basic Health Units (UBS), based on a sample stratified by region and by conglomerate in a single stage. Data collection took place between September and October 2021, through a self-completed questionnaire during the period that the user was waiting for service at the UBS. Traumatic experiences were evaluated using the Childhood Trauma Questionnaire (QUESI), and their distribution according to sociodemographic, family, childhood and adolescence characteristics, in addition to health information, such as self-rated health and common mental disorders. The chi-square and Fisher's exact tests were used to assess the association between the variables, adopting a significance level of 5%. Results: 463 people were interviewed, most of them female (81.7%), black or mixed race (55.6%) and with a partner (55.5%). The overall prevalence of childhood traumatic experiences from non-existent to minimal was 29.4%, and from low to moderate trauma was 55.5%. It was estimated that 78.8% of participants experienced at least one type of abuse or neglect during childhood. There was a prevalence of 9.7% for physical abuse, 7.1% for sexual abuse, 9.5% for emotional abuse, 59.8% for physical neglect and 38.9% for emotional neglect. The prevalence of abuse and emotional neglect was higher among those who reported the absence of both or one of the biological parents at upbringing, parental divorce before age 12, stressors during childhood, such as witnessing many fights and being sent away or having left at home with parents, who rated their health as poor or very poor, who use psychiatric medication, with common mental disorders and negative aspects of sexual health. Conclusion: This study offers elements for the knowledge of the prevalence and distribution of traumatic experiences in childhood in the population of users of primary care in Cuiabá. This estimate points to the occurrence of these experiences that must be considered in health practices at the individual and collective levels, insofar as it subsidizes the planning of public policies for prevention and health promotion.